ORGANIZACJA ‘CURA URBIS’ W RZYMIE W POCZĄTKACH PRYNCYPATU - Kamińska, Renata (Zeszyty Prawnicze, 2016)
THE ORGANISATION OF THE ‘CURA URBIS’ IN ROME AT THE BEGINNING OF THE PRINCIPATE Summary When Augustus assumed power changes started to be implemented in the Roman public administration. Some of them affected the administration of the city. The cura urbis, which under the Republic had been one of the duties of the aedils and censors, now passed to the powers of the curators, who were liable for most of the business relating to the proper functioning of the City, its order and security. The curatores worked as a collegial body; they were appointed by the princeps and were accountable to him. The most important and characteristic curatorial colleges at the beginning of the principate were the curatores aquarum, the curatores riparum et alvei Tiberis, the curatores aedium sacrarum et operum locorumque publicorum and the curatores viarum.